2021
DOI: 10.3390/ijerph182211935
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Stay-at-Home Restrictions on Employment Status, Physical Activity, and Sedentary Behavior

Abstract: Background. North Americans report insufficient moderate-to-vigorous physical activity (MVPA) and ample sedentary behaviors (SBs), suggesting possible barriers to an active lifestyle. This study compared self-reported MVPA and SB before and during COVID-19 “Stay-at-Home” restrictions as a potential barrier across North America. Methods: Questionnaires were distributed from 21 April to 9 May 2020. ANOVAs compared data overall and by group (age, sex, race, income, education, employment status). Results: During r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
1
13
0
6
Order By: Relevance
“…For others, however, working from home detrimentally impacted health behavior and well-being. For example, it is well-documented that physical activity decreased and sedentary behaviors increased among home workers during the pandemic 43–45 . Our participants reported that the discontinuation of in-person communication during the lockdown rendered day to day working practices entirely dependent on digital interfaces (see too 46 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For others, however, working from home detrimentally impacted health behavior and well-being. For example, it is well-documented that physical activity decreased and sedentary behaviors increased among home workers during the pandemic 43–45 . Our participants reported that the discontinuation of in-person communication during the lockdown rendered day to day working practices entirely dependent on digital interfaces (see too 46 ).…”
Section: Discussionmentioning
confidence: 85%
“…For example, it is well-documented that physical activity decreased and sedentary behaviors increased among home workers during the pandemic. [43][44][45] Our participants reported that the discontinuation of in-person communication during the lockdown rendered day to day working practices entirely dependent on digital interfaces (see too 46 ). Home-workers experienced a greater number of online meetings, and many described feeling pressured to be visibly online throughout the day to demonstrate to colleagues that they were working.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students in Taiwan experienced significant deficits in clinical emergency training [ 31 ]. Lockdowns and school closures have also been linked to decreases in physical activity and substantial increases in screen time and negative emotions [ 32 , 33 , 34 ].…”
Section: Covid-19 Pandemic Responsementioning
confidence: 99%
“…When workers shift from workplace work to telework, health issues may arise. Several previous studies indicated that telework leads to decreased physical activity, [8][9][10][11][12][13] increased screen time, 9,14 unhealthy eating habits, such as snacking, and increased alcohol consumption. 9,[13][14][15] These lifestyle changes of workers may result in their weight gain or a deterioration in their mental health, such as isolation, loneliness, and work-family conflict.…”
mentioning
confidence: 99%
“…9,[13][14][15] These lifestyle changes of workers may result in their weight gain or a deterioration in their mental health, such as isolation, loneliness, and work-family conflict. 14,[16][17][18][19][20] However, most previous studies on this point have been cross-sectional studies [8][9][10][12][13][14][15][16][17]19,20 using self-administered questionnaires, [8][9][10][12][13][14][15][16][17][19][20][21] and there have been few studies using objectively measured data with a longitudinal study design, although such studies are crucial to clarify the details of the health effects of telework. Therefore, in this study, we longitudinally analyzed the changes in physical health before and after the introduction of telework among Japanese workers.…”
mentioning
confidence: 99%